2020
DOI: 10.1109/tcomm.2020.2990951
|View full text |Cite
|
Sign up to set email alerts
|

Downlink Spectral Efficiency of Cell-Free Massive MIMO Systems With Multi-Antenna Users

Abstract: This paper studies a cell-free massive multiple-input multiple-output (MIMO) system where its access points (APs) and users are equipped with multiple antennas. Two transmission protocols are considered. In the first transmission protocol, there are no downlink pilots, while in the second transmission protocol, downlink pilots are proposed in order to improve the system performance. In both transmission protocols, the users use the minimum mean-squared error-based successive interference cancellation (MMSE-SIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 34 publications
1
63
0
Order By: Relevance
“…The channel gain between k th UE and n th antenna of l th AP is given by Mai et al 18 glnk=LlnkbFlnk12hlnk …”
Section: Radio Stripe Network Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The channel gain between k th UE and n th antenna of l th AP is given by Mai et al 18 glnk=LlnkbFlnk12hlnk …”
Section: Radio Stripe Network Modelmentioning
confidence: 99%
“…Analysis of cell‐free mMIMO has been carried out mainly for SE and energy efficiency 16‐20 . Other important performance metrices such as probability of outage are difficult to derive exactly in closed form 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In cell-free massive MIMO systems, all APs are connected and cooperate with the central processing unit through a fronthaul network to provide services for all users through time division duplex technology on the same time-frequency resources [2]. Considering the large-scale deployment of APs, cell-free massive MIMO systems have favourable propagation and channel hardening characteristics, so they have significant advantages in spectral efficiency [3]. However, the benefits of cell-free massive MIMO come at the expense of increased fronthaul capacity requirements.…”
Section: Introductionmentioning
confidence: 99%
“…However, in [8], multiple‐antenna APs have been analysed in order to improve channel hardening and to increase the likelihood that favourable propagation occurs. In the same way, [23] explores the downlink spectral efficiency in a scenario with multiple‐antenna APs and users. Additionally, in [24] it is shown that, in terms of costs, it is better to add more antennas to an AP than to install more APs.…”
Section: Introductionmentioning
confidence: 99%